Protein Kinase C δ Regulates the Depletion of Actin at the Immunological Synapse Required for Polarized Exosome Secretion by T Cells - Herranz, Gonzalo; Aguilera, Pablo; Dávila, Sergio; Sánchez, Alicia; Stancu, Bianca; Gómez, Jesús; Fernández-Moreno, David; de Martín, Raúl; Quintanilla, Mario; Fernández, Teresa; Rodríguez-Silvestre, Pablo; Márquez-Expósito, Laura; et al. (Frontiers in Immunology, 2019)
Multivesicular bodies (MVB) are endocytic compartments that enclose intraluminal vesicles (ILV) formed by inward budding from the limiting membrane of endosomes. In T lymphocytes, ILV are secreted as Fas ligand-bearing, pro-apoptotic exosomes following T cell receptor (TCR)-induced fusion of MVB with the plasma membrane at the immune synapse (IS). In this study we show that protein kinase C δ (PKCδ), a novel PKC isotype activated by diacylglycerol (DAG), regulates TCR-controlled, MVB polarization towards the IS and exosome secretion. Concomitantly, we demonstrate that PKCδ-interfered T lymphocytes are defective in activation-induced cell death. Using a DAG sensor based on the C1 DAG-binding domain of PKCδ and a GFP-PKCδ chimera, we reveal that T lymphocyte activation enhances DAG levels at the MVB endomembranes that mediates the association of PKCδ to MVB. Spatiotemporal reorganization of F-actin at the IS is inhibited in PKCδ-interfered T lymphocytes. Therefore, we propose PKCδ as a DAG effector that regulates the actin reorganization necessary for MVB traffic and exosome secretion.